2012
DOI: 10.1111/j.1469-185x.2012.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Diptera vectors of avian Haemosporidian parasites: untangling parasite life cycles and their taxonomy

Abstract: Haemosporida is a large group of vector-borne intracellular parasites that infect amphibians, reptiles, birds, and mammals. This group includes the different malaria parasites (Plasmodium spp.) that infect humans around the world. Our knowledge on the full life cycle of these parasites is most complete for those parasites that infect humans and, to some extent, birds. However, our current knowledge on haemosporidian life cycles is characterized by a paucity of information concerning the vector species responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
279
1
24

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 303 publications
(310 citation statements)
references
References 268 publications
1
279
1
24
Order By: Relevance
“…Specifically, the infection risk is determined by the relative abundance of vectors; the more vectors present, the higher the infection risk. In addition, vectors are habitat-dependent, mostly on habitats with mild temperatures and a minimum range of humidity, for reproduction (Santiago-Alarcon et al, 2012). Additionally, we suggest that competition for territories will negatively affect adult condition, as well as the development of hatchlings and fledglings, because when infected they have to devote resources to combat parasites.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Specifically, the infection risk is determined by the relative abundance of vectors; the more vectors present, the higher the infection risk. In addition, vectors are habitat-dependent, mostly on habitats with mild temperatures and a minimum range of humidity, for reproduction (Santiago-Alarcon et al, 2012). Additionally, we suggest that competition for territories will negatively affect adult condition, as well as the development of hatchlings and fledglings, because when infected they have to devote resources to combat parasites.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, vector presence and abundance will co-determine the infection risk of vector-borne parasites at any given place (Santiago-Alarcon et al, 2013a, b). The higher the number of parasites transmitted from vector to host, the greater the chance that parasites can actually infect the host -a low parasite dose might be more effectively counteracted by the host's immune defense than a higher one (Santiago-Alarcon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Mooswald forest we have investigated Culicoides vectors (Santiago-Alarcon et al 2012a, 2013a, which are implicated in the transmission of Haemoproteus parasites (Valkiūnas 2005;Santiago-Alarcon et al 2012b). We have shown that most species of Culicoides, even those previously considered ornithophilic, are generalists taking blood meals from both mammals and birds (Santiago-Alarcon et al 2012a, 2013a.…”
Section: Discussionmentioning
confidence: 97%
“…Although Ad. squamipennis has never been found infected with avian Plasmodium in Brazil (Santiago-Alarcon et al 2012), this record in Santo Amaro do Maranhão indicates some epidemiological potential. The municipality lies on the Santo Amaro Lake, which borders the western edge of the Lençóis Maranhenses National Park.…”
mentioning
confidence: 99%
“…It is known that vector susceptibility to a parasite species can vary among populations, a phenomenon that may be explained by a combination of environmental conditions and ecological factors potentially altering vector-pathogen-host interactions (Santiago-Alarcon et al 2012), in addition to behavioral and ecological variation. Although Ad.…”
mentioning
confidence: 99%